Assessment of a low-enthalpy geothermal resource and evaluation of the natural CO2 output in the Tor di Quinto area (Rome city, Italy). (February 2022) - Carapezza, Maria Luisa; Chiappini, Massimo; Nicolosi, Iacopo; Pizzino, Luca; Ranaldi, Massimo; Tarchini, Luca; De Simone, Gabriele; Ricchetti, Nicoletta; Barberi, Franco
Highlights: Assessment of a shallow low-enthalpy geothermal resource within the city of Rome. Evaluation by ERT profiles of top depth (∼40 m) and thickness (∼20 m) of the aquifer. Geothermal water has high salinity and dissolved CO2 and a constant T of 17.5 °C. This Rome sector has a high diffuse soil CO2 output of 87.77 t*day −1 from 3 km 2 . Water heat exchangers and geothermal heat pump appear convenient for exploitation. Abstract: Rome Capital City is located in a high heat flux area of central Italy, suitable for low-enthalpy geothermal exploitation. In the central-northern part of the city, near Tor di Quinto hippodrome close to Tiber River, a wide undeveloped area occurs, which is a possible future urban development site. We present the results of a geochemical and geophysical study aimed at assessing the presence in this zone of a low-enthalpy geothermal aquifer and at evaluating its depth, thickness and the physico-chemical characteristics of the geothermal water. Furthermore the natural CO2 output of this zone has been investigated. A soil CO2 flux survey with 551 measurements over a surface of 3.09 km 2 revealed the presence of parallel NW-SE trending positive flux anomalies. The total CO2 output was estimated to 87.77 t*day −1, most of which (85%) of endogenous or mixed origin. An Electrical Resistivity Tomography survey, consisting of five parallel 355 m long and 100 m spaced profiles, allowed the reconstruction of the stratigraphy of the underground sediments, which are fluvial deposits of the near Tiber River. The geothermal water is hosted in a low-resistivity layer, corresponding to the Tiber base gravels, which are here 20 m thick and whose top is 40 m below the surface. The water has a nearly constant temperature of 17.5 °C, a relatively high salinity and an appreciable content in dissolved gas. This low-enthalpy resource is suitable for direct uses, e.g. individual and district heating/cooling, sanitary hot water, spa facilities for swimming and bathing.